A Marketplace System Web-Based Using The Extreme Programming Method - Hadaya, M. Syahan Afdhal; Utomo, Pradita Eko Prasetyo; Bintana, Rizqa Raaiqa (Jurusan Informatika Universitas Tanjungpura, 2025)
This study aims to design and develop a web-based marketplace information system for X University using the Extreme Programming methodology while also evaluating the functionality of its features. The selected method, Extreme Programming (XP), focuses on rapid iterative development and effective communication with stakeholders. The system was successfully designed and developed through three iterative cycles. During the first iteration, development was conducted by implementing the pre-planned design based on the established release plan. The second iteration continued with the same development process, adhering to the outlined steps in the release plan. In the third iteration, additional actors and new features were incorporated into the system. To assess the system